The Antibacterial Activity Testing on Acetyleugenol Against Staphylococcus aereus - Dinurrosifa, Rahmawati Salsa; Sulistyarini, Indah; Darumas P, Athika; Indriyanti, Erwin (Al-Kimia, 2023)
The main contents of clove oil are phenolic compounds, namely eugenol, eugenol acetate and gallic acid, as well as flavonoids. One of the derivatives of the eugenol compound is acetyl eugenol which was developed by the esterification reaction between eugenol and acetic acid anhydride using the sonochemical method. Synthesis of acetyleugenol was sonicated for 30 minutes at a temperature of 70-80°C. The % yield of the synthesized compound is calculated and continued with testing which includes solubility, melting point, FTIR and GC-MS tests, which are then tested for antimicrobial activity. The research results show that eugenol and acetic acid anhydride compounds with a NaOH catalyst can be synthesized using ultrasonic waves and produce a % yield of 3.50%. The resulting synthesis can melt starting at a temperature of 30°C and can dissolve in ethanol, methanol, chloroform and ether but does not dissolve in distilled water. FTIR testing on the acetyl eugenol compound showed the presence of -OH phenolic groups, C=C alkenes, C=C aromatics, C-O esters, and C=O esters. Acetyleugenol at concentrations of 1.25%, 2.5%, 5%, and 10% was able to act antibacterial on Staphylococcus aureus cultures with a density of 1.0 X 108 CFU/mL.